E-193 Endovascular treatment for idiopathic intracranial hypertension. A single center series. (23rd July 2022) - Rustici, A; Cancelliere, N; Vanek, I; Marotta, T; Spears, J; Mendes Pereira, V
Abstract : Introduction: Idiopathic intracranial hypertension (IIH) is a disease which has a significant impact on patients' quality of life and if untreated, can lead to vision loss. To date, there is no consensus on the best treatment strategy for IIH. The cause of IIH is unknown but the presence of venous sinus stenosis (VSS) can contribute to the disease development or worsening. Recently, endovascular treatment with Venous Sinus Stenting (VSSt) for IIH has been used with success. Materials and Methods: We included all patients with clinical diagnosis of IIH treated in our center with VSSt from January 2020 to December 2021. Patient diagnosis was confirmed with lumbar puncture and they were followed with regular neuro-ophthalmological evaluation. Results: We included thirty-four patients that underwent endovascular venous stenting for the treatment of IIH. The median age of patients was 34 ± 9.4 years and all patients were females. The indication for VSSt treatment was the failure of other surgical and medical treatment in the 20.6% of cases, the failure of medical treatment in 47.1% of cases and symptoms significantly affecting patient's quality of life in 32.3% of cases. In 61.8% of cases there was a unilateral stenosis requiring a single-side procedure, whereas in 38.2% of cases were treated with a bilateral stenting. No patients required a second treatment with stenting in this series. Symptoms improved in 64.7% of patients. The 14.7% patients required an additional surgical procedure. All procedures were successful without intraoperative complications. In only one case (2.9%) an acute postoperative venous infarction was detected 24 hours after the procedure. No permanent morbidity or mortality was recorded. Conclusion: Venous sinus stenting is a safe and effective treatment for IIH that may provide substantial clinical improvement, particularly when other surgical and medical treatments had fail. Disclosures: A. Rustici: None. N. Cancelliere: None. I. Vanek: None. T. Marotta: None. J. Spears: None. V. Mendes Pereira: None.